Systematic Evaluation of Women With Suspected Endometriosis Using a 5‐Domain Sonographically Based Approach. (1st June 2015) - Menakaya, Uche; Reid, Shannon; Infante, Fernando; Condous, George
Abstract : In recent years, knowledge has evolved regarding the role of transvaginal sonography in the assessment of the pouch of Douglas status and the preoperative prediction of extraovarian endometriosis in specific locations. Despite these advances in transvaginal sonography, the challenge of developing a comprehensive, cost‐effective, and reproducible preoperative classification system for endometriosis remains. Critical to this classification system should be a sonographically based evaluation protocol that is systematic, evidence based, and reproducible with clearly defined end points. To date, no structured evaluation protocol exists for the assessment of the pelvis in women with suspected endometriosis. In this article, we propose a domain‐based evaluation protocol for the assessment of women with suspected endometriosis using transvaginal sonography.